2010
DOI: 10.1039/c004707d
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-controlled cell aggregation in a multi-well chip

Abstract: We demonstrate a microplate platform for parallelized manipulation of particles or cells by frequency-modulated ultrasound. The device, consisting of a silicon-glass microchip and a single ultrasonic transducer, enables aggregation, positioning and high-resolution microscopy of cells distributed in an array of 100 microwells centered on the microchip. We characterize the system in terms of temperature control, aggregation and positioning efficiency, and cell viability. We use time-lapse imaging to show that ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 24 publications
(30 reference statements)
3
122
0
Order By: Relevance
“…To date, many acoustic-based particle manipulation functions (e.g., focusing, separating, sorting, mixing, and patterning) have been realized (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). None of these approaches, however, have achieved the dexterity of optical tweezers; in other words, none of the previous acoustic-based methods are capable of precisely manipulating single microparticles or cells along an arbitrary path in two dimensions.…”
mentioning
confidence: 99%
“…To date, many acoustic-based particle manipulation functions (e.g., focusing, separating, sorting, mixing, and patterning) have been realized (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). None of these approaches, however, have achieved the dexterity of optical tweezers; in other words, none of the previous acoustic-based methods are capable of precisely manipulating single microparticles or cells along an arbitrary path in two dimensions.…”
mentioning
confidence: 99%
“…The viability of mammalian cells held by ultrasonic forces within a mesh has been shown to be retained [69] and erythrocytes exposed to acoustic field strengths high enough to induce mixing showed no significant damage [69]. Hultström et al [70] suspended aggregates of cells in a flowing culture medium within a microfluidic chip and showed that not only their viability, but also their ability to proliferate was maintained and the same group demonstrated that cells exposed to ultrasound in a multi-well micro-plate for three days retained the potential to proliferate [50]. A series of papers by Bazou and co-workers has examined the behaviour of ultrasonically suspended cell aggregates [71,72] and have shown that embryonic stem cells levitated in an ultrasonic field for an hour retain pluripotency and their gene expression is unmodified [73].…”
Section: Cell Viabilitymentioning
confidence: 93%
“…The additional control offered by incorporating ultrasound manipulation techniques within existing experimental protocols offers significant opportunities to accelerate early stage drug development. The manipulation techniques outlined above provide the means to coordinate delivery of materials across multiwell plates [50] for parallel investigation and aggregate drugs, cells or combinations of each to control and initiate interactions at specific time points. The results could improve experimental throughput by orders of magnitude reducing development times and perhaps enabling more comprehensive investigations.…”
Section: Study Of Drug-cell Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuznetsova et al investigated channel designs with height h =4, which led, in combination with an appropriate reflector thickness, to a pressure node located at a different position from the midchannel [7]. In addition to the layered design with axial or transverse stimulation, Wiklund et al worked on a device with multiple piezo parts orthogonally glued to the reflector: they achieved tree-dimensional (3D) handling of particles with a single focus in the middle of the channel [8,9]. Haake et al used shear transducers to aggregate particles into lines and points [10,11].…”
Section: Introductionmentioning
confidence: 99%